A new species and immature stages of the skiff beetle genus Yara Reichardt and Hinton (Coleoptera: Myxophaga: Hydroscaphidae) from Nicaragua - Reyes, Scarleth Margarita Raudez; Espinoza, Roberto Antonio Cano; Girón, Jennifer C. (Zootaxa, 2019)
Yara marmontsedu, a new species in the family Hydroscaphidae (Coleoptera: Myxophaga), is described and illustrated. Specimens of Y. marmontsedu were collected at the Pijibay Creek, tributary of the Mico River in Chontales, Nicaragua. The immature stages are described and illustrated for the first time for a species of Yara. This is a contribution to the knowledge of the water beetle fauna of Nicaragua.